Raising and mobilising skills to boost productivity and inclusiveness in Belgium - Vandenberghe, Vincent (OECD Economics Department Working Papers, 2017)
A highly educated and skilled workforce has been an important driver of productivity performance and prosperity in Belgium. This paper examines skills policies that could help improve productivity and inclusiveness. An increased focus on lifelong learning, improved and more flexible working conditions for older workers, and a more efficient allocation of students and skills would benefit productivity growth. Improving inclusiveness requires increasing access and participation in tertiary education, especially for students with disadvantaged backgrounds. Digitalisation holds the promise of large gains in labour productivity, but is disrupting the nature of employment relationships. It calls for measures that encourage information and communication technology (ICT) upskilling and for adapting tax and benefit systems to the rise of on-demand jobs linked to the use of e-platforms